2013
DOI: 10.1016/j.neuroimage.2013.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in thickness, and folding developments throughout the cortex

Abstract: While significant differences in male and female brain structures have commonly been reported, only a few studies have focused on the sex differences in the way the cortex matures over time. Here, we investigated cortical thickness maturation between the age of 6 to 30 years, using 209 longitudinally-acquired brain MRI scans. Significant sex differences in the trajectories of cortical thickness change with age were evidenced using non-linear mixed effects models. Similar statistical analyses were computed to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
168
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(194 citation statements)
references
References 52 publications
23
168
2
1
Order By: Relevance
“…healthy children, adolescents and young adults, Mutlu et al (2013) found a linearly decreasing lGI with age in most cortical regions, with the exception of the medial prefrontal and cuneus/precuneus regions where lGI did not correlate with age. As such, the localization of our two clusters with decreased lGI with age and the cluster without significant age-related decrease is largely in agreement with the topological distribution of the trajectories reported by Mutlu et al The absence of significant age × diagnosis interaction effect in the present study suggests that group differences in lGI are independent of age.…”
Section: Relationship With Agementioning
confidence: 78%
“…healthy children, adolescents and young adults, Mutlu et al (2013) found a linearly decreasing lGI with age in most cortical regions, with the exception of the medial prefrontal and cuneus/precuneus regions where lGI did not correlate with age. As such, the localization of our two clusters with decreased lGI with age and the cluster without significant age-related decrease is largely in agreement with the topological distribution of the trajectories reported by Mutlu et al The absence of significant age × diagnosis interaction effect in the present study suggests that group differences in lGI are independent of age.…”
Section: Relationship With Agementioning
confidence: 78%
“…However, Possible gender related associations between brain morphology and Internet habits should be further investigated as sexual dimorphism in the brain structure can contribute to behavioural differences (Mutlu et al 2013;Sun et al 2015). Longitudinal studies are highly needed to test whether these structural correlates are the result of overall additive tendencies or specific to maladaptive Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…54 Also, cortical TPJ thinning during adolescence is localized to the left hemisphere. 35 Nevertheless, we observed bilateral STS grey matter reductions in women with anorexia nervosa and found trends toward associations between TPJ grey matter volume and autistic traits bilaterally. Any lateralization should therefore be interpreted with caution, and further studies in larger samples are required to confirm such effects.…”
Section: Discussionmentioning
confidence: 49%
“…52 Notably, healthy girls exhibit a higher rate of cortical thinning of social brain regions during adolescence than boys, including thinning of the right temporal cortex and the left TPJ. 35 Our findings raise the possibility that adolescent onset of anorexia nervosa may be linked to such cortical developments. However, further studies directly comparing boys and girls with anorexia nervosa are required to characterize shared and distinct alterations; this is a particularly difficult challenge given the low prevalence of anorexia nervosa in boys.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation